Uncovering The Needs for Local Culture-Based Audiovisual Media in EFL Teaching to Promote Students’ Cultural Awareness - Raudhatul Jannah; Machdalena Vianty; Eryansyah Eryansyah (Universitas Islam Negeri Madura, 2026)
Abstract : Local culture holds a crucial position in English as a Foreign Language (EFL) learning, particularly in fostering students’ cultural awareness and supporting meaningful language use. However, English instructional materials at the junior high school level often provide limited integration of students’ local cultural contexts, which may reduce learners’ engagement and comprehension. This study aims to conduct a needs analysis on the integration of local culture–based audiovisual media in EFL teaching as a foundation for designing appropriate instructional media for seventh-grade students who are beginning formal English learning. Specifically, the study investigates the needs and preferences of seventh-grade students and English teachers at SMP IT Harapan Mulia Palembang regarding the use of audiovisual media to support reading comprehension and promote cultural awareness. A mixed-methods approach was employed in this study. Questionnaires were administered to 130 seventh-grade students, while semi-structured interviews were conducted with two English teachers. The findings reveal that students prefer audiovisual media over text-based materials and show higher motivation in English learning when local cultural content is incorporated. Students also experience difficulties in understanding main ideas and detailed information in reading texts, which are associated with low engagement with culturally unfamiliar topics. Teachers support the integration of local culture–based audiovisual media but report limited availability of suitable instructional resources. In conclusion, the study highlights the need to develop local culture–based audiovisual media to support EFL instruction, enhance reading comprehension, and foster students’ cultural awareness at the junior high school level.